Differential Approach to the Educational Process as a Specific Form of Humanism - Ochilov Akmal Eshtemirovich (Researchparks Publishing, 2022)
In this country, the features of a differentiated approach to the development of intellectual characteristics to students, the formation of knowledge, intellectual and intellectual activity in the organization of the educational process, i.e. educational process based on the human idea.